2019
DOI: 10.1016/j.anai.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The Asthma Controller Step-down Yardstick

Abstract: Asthma guidelines recommend a control-based approach to disease management in which the assessment of impairment and risk is linked to step-based therapy. Using this model, controller treatment is adjusteddupward or downwarddaccording to a patient's level of asthma control over time. Strategies for stepping up controller therapy are well described, and the adult and pediatric Asthma Yardsticks provide operational recommendations based on patient profiles. Strategies for stepping down controller treatment are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 154 publications
(243 reference statements)
1
12
0
1
Order By: Relevance
“…the tapering algorithm is not the subject of study per se) and results in a diverse selection of study-specific algorithms (19)(20)(21)(22)(23)(24)(25)(26), whose detail varies significantly between published studies. Current recommendations (4,27) do not provide guidance on the choice of OCS tapering protocol or otherwise how to taper. From a clinical perspective, the lack of asthma-specific guidelines on OCS tapering and the systematic screening of adverse events represents a key barrier to reducing OCS use (16).…”
Section: Introductionmentioning
confidence: 99%
“…the tapering algorithm is not the subject of study per se) and results in a diverse selection of study-specific algorithms (19)(20)(21)(22)(23)(24)(25)(26), whose detail varies significantly between published studies. Current recommendations (4,27) do not provide guidance on the choice of OCS tapering protocol or otherwise how to taper. From a clinical perspective, the lack of asthma-specific guidelines on OCS tapering and the systematic screening of adverse events represents a key barrier to reducing OCS use (16).…”
Section: Introductionmentioning
confidence: 99%
“…Community pharmacists answered a shorter sixitem (one page) version of the survey. The questionnaires and interviews were first discussed with knowledgeable key informants (face validity) before drawing up a question guide which was piloted, developed, modified and informed by a review of the literature [9][10][11][12] (Supplementary Table 1). Respondents were able to review and change their answers.…”
Section: Data Collectionmentioning
confidence: 99%
“…The cornerstone of treatment for persistent asthma is the stepwise adjustment of medication depending on the extent of asthma control 1 . Many studies 2‐5 and review articles 6,7 reported change of lung function and asthma control after withdrawal of inhaled corticosteroids (ICSs), as stepping down from step‐2 treatment of adults or/and children with stable and mild asthma 8‐12 . However, there is little information on pulmonary function and asthma control after the withdrawal of a leukotriene receptor antagonist (LTRA) in children who have well‐controlled mild persistent asthma 13 .…”
Section: Introductionmentioning
confidence: 99%